Pelatihan Pemanfaatan Media Pembelajaran Presentasi Berbasis Animaker terhadap Hasil Belajar - Hadi Gunawan Sakti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Technological advances have a major impact on the world of education, especially in changing the pattern of interaction between teachers and students. This encourages teachers to continue to innovate in the use of technology, including in the use of learning media. The right media can increase the effectiveness of delivering material and create a fun learning atmosphere. This community service activity aims to improve the ability of SDN 5 Lepak, East Sakra District, East Lombok Regency teachers in developing learning media based on Animaker, an interactive and interesting animation creation platform. The method used is participatory training consisting of the stages of coordination, preparation, implementation, and evaluation. The activity was accompanied by a team of lecturers directly. The results of the training showed that 88% of participants succeeded in developing learning media using Animaker very well. In addition, participants showed high enthusiasm and increased understanding of digital learning technology. However, the challenges faced include limited devices and internet connections. This activity contributes to improving teacher competence, as well as encouraging more creative and student-centered learning.